(untitled) (Research, Society and Development, 2022)
The present study aimed to identify the social representation of the dental surgeon from cinematographic productions in undergraduate courses on the health sciences through a quantitative-qualitative approach. The methodology consisted of the presentation of three movies that had the dentist as a character (O Homem do Ano (Conspiração Filmes and Warner Bros, 2003; Charlie and the Chocolate Factory (Warner Bros, 2005) and The Hangover I (Warner Bros., 2009)). The exhibitions took place in the classroom, at different times, for students from the Dentistry, Nursing, and Physiotherapy courses. After the movie presentation, the volunteers answered a questionnaire containing alternative and essay questions. The alternative answers were expressed as percentages, while the essay questions were grouped and expressed by common and repeated keywords. The data were grouped according to the movie presented and/or analyzed course, depending on the question addressed. 56.2% of the individuals sampled are unsatisfied with the image that the media has been conveying of the dental surgeon; however, only dental students reported that this could reflect in professional aspects. The “The Hangover I” movie was considered the one that could be the most damaging to professional class. It is concluded, therefore, that there was unsatisfaction about the image that the media in general, including movies, have been showing about dental profession.